Peran Media Relations terhadap Keberhasilan Program Provocative Proactive di Pt Media Televisi Indonesia (Metro Tv) - Marta Sanjaya; Ariesza Sekarayu Larasati (Humaniora, 2013)
This article aims to determine whether the Provocative Proactive (PP) program on Metro TV proactive is known by Indonesian people, to explain how the media selection strategy for Provocative Proactive program is, and to explain the program on Metro TV can be written and known by the press or reporters (external PR). The method used was descriptive qualitative approach to analyze the existing problems by presentation of information from the data collected through the company's internal analysis of the results of in-depth interviews and field observations regarding activities in the company. The results showed that duties and functions of public relations are as a motor for better co-operation with external and internal parties relating to Provocative Proactive program. The PR and Promotion Departments were turned out to help the success of the PP program, in addition to various roles and hardworks of the Producer and the creative team. Based on the observations, the role of Metro TV’s PR and Promotion Departments in conducting media relations through cooperation with the media both print and electronic media in an effort to have Provocative Proactive widely known by the public is through cooperation with various mass media, implementation of mass media selection strategies, and introducing Provocative Proactive Program broadly.